Design analysis of exterior car body part - Bastian Wibar, Momang (2013)
The existing designs of the car panel need to be studied by digitizing the surface of the panel of various car models. This research focuses on the static simulation analysis especially to strain, stress and displacement analysis of a front fender panel of the car. The main objectives of this research are to study the design of the existing exterior car body part, analyze and proposed the mechanism to improve the design using Finite Element Method software. To achieve that, three different designs of front fender panel were used, there are Proton Iswara, Honda EG and Proton Saga front fender panel. A 3D Scanner machine used to scan the actual model of front fender panel and to convert the model into the simulation analysis format by using POLYWORK software. SOLIDWORKS software was used to create corner radius and surface of the front fender panel of the car. After that, analysis was carried out by using commercial Finite Elements software ( ALGOR)to evaluate and analyze the behavior and surface of a front fender panel of the car. It is considered the function, design, strength and the rigidity of the stamping parts of the front fender panel. In this research, this front fender panel analyzed using the static simulation analysis for components with linear materials. For this simulation, two types of load will be applied on the surface of the front fender panel which are at all surface area and at selected surface area. The result will be analyzed based on the strain, stress and the displacement of the surface of the front fender panel. The comparison of strain, stress and displacement data of each car front fender model were done using graphs. With this, the process of digitizing the surface of the front fender model can be done easily. After that, a related study was carried out to know the properties of the front fender panel during the impact of the applied load. At the end of this research, the comparison data of various car front fender panels will be known and could be the basis for the future design. Besides that, the area between the optimum line and the minimum line for each graph analysis can be used as a guideline and a mechanism to improve the design of front fender panel in the future.